Quantitative Proteomic Analysis of Wheat Cultivars with Differing Drought Stress Tolerance - Ford, Kristina L.; Cassin, Andrew; Bacic, Antony (Frontiers in Plant Science, 2011)
Using a series of multiplexed experiments we studied the quantitative changes in protein abundance of three Australian bread wheat cultivars (Triticum aestivum L.) in response to a drought stress. Three cultivars differing in their ability to maintain grain yield during drought, Kukri (intolerant), Excalibur (tolerant) and RAC875 (tolerant), were grown in the glasshouse with cyclic drought treatment that mimicked conditions in the field. Proteins were isolated from leaves of mature plants and isobaric tags were used to follow changes in the relative protein abundance of 159 proteins. This is the first shotgun proteomics study in wheat, providing important insights into protein responses to drought as well as identifying the largest number of wheat proteins (1,299) in a single study. The changes in the three cultivars at the different time points reflected their differing physiological responses to drought, with the two drought tolerant varieties (Excalibur and RAC875) differing in their protein responses. Excalibur lacked significant changes in proteins during the initial onset of the water deficit in contrast to RAC875 that had a large number of significant changes. All three cultivars had changes consistent with an increase in oxidative stress metabolism and ROS scavenging capacity seen through increases in superoxide dismutases and catalases as well as ROS avoidance through the decreases in proteins involved in photosynthesis and the Calvin cycle.